A CRM1 Inhibitor Alleviates Cardiac Hypertrophy and Increases the Nuclear Distribution of NT-PGC-1α in NRVMs - Liu, Zuheng; Tian, Haiping; Hua, Jinghai; Cai, Wanqiang; Bai, Yujia; Zhan, Qiong; Lai, Wenyan; Zeng, Qingchun; Ren, Hao; Xu, Dingli (Frontiers in Pharmacology, 2019)
CRM1 (chromosomal maintenance 1) inhibitor displays anti-hypertrophy effect and controls protein trayfficking between nucleus and ctoplasm. PGC-1α is a kind of transcriptional factor co-activator which residing in nucleus predominantly and was down-regulated during heart failure. NT-PGC-1α is an alternative splicing variant of PGC-1α, which primarily distributes in cytoplasm. We hypothesis that shuttling NT-PGC-1α into nucleus by CRM1 inhibitor would probably active downstream targets of PGC-1α in nucleus and improve cardiac function in myocardial infarction mice. PGC-1α and NT-PGC-1α were decreased in myocardial infarction (MI)-induced heart failure mice. The anti-hypertrophy effect of CRM1 inhibitor Selinexor was verified by the expression of β-MHC and the visualization of cell cross-sectional area. After neonatal rat cardiomyocytes (NRCMs) transfected with adenovirus-NT-PGC-1α or adenovirus-NLS-NT-PGC-1α, they were exposed to Selinexor. Then, the shuttling of NT-PGC-1αwere observed by confocal microscopy. After NT-PGC-1α shuttling into nucleus, the expression of relative genes were increased (including PPAR-α, Tfam, ERR-γ, CPT1b, PDK4 and Nrf2). The effects of Selinexor on post-MI C57BL/6j mice were determined by echocardiography and qPCR. We found that Selinexor showed anti hypertrophy effect, but it did not influence ejection fraction in MI-mice. Selinexor displayed anti-hypertrophy effects, and participated in the transportation of NT-PGC-1α.